The relationship between fatigue, stress and job performance with some demographic variables in dental prosthesis technicians - Bahram Kouhnavard; Hosseinali Mahgoli; Somayeh bolghanabadi; Mohsen Yazdan Aval; Maryam Rostami Aghdam Shendi; Malihe Kolahdouzi (Tehran University of Medical Sciences, 2018)
Background and Aims: Making dental prostheses is sensitive and accurate work and requires powerful and skilled hands. Because of this, the dental prosthesis technicians may suffer harmful effects such as stress and fatigue during the course. The aim of this study was to investigate fatigue, stress and job performance and their relationship with some demographic variables in this community. Materials and Methods: The present study was cross-sectional and done in 2016. The study population was a group of dental prosthesis technicians that had participated in a national congress in Tehran. Sampling was done by census Two standardized questionnaires on the subjects of fatigue and stress which were distributed among 100 female and male participants and sampling was done by census. Then, the obtained data was analyzed using SPSS16 software and applying descriptive statistics, Pearson correlation test, and ANOVA, T-test. Results: From the 100 samples, there were 16 females and 84 males with mean age 34.71±7.90 and average work experience of 10.82± 9.01 years. 82 percent of the subjects were married and 42 percent of them were smokers. The results showed that 100 percent of dental prostheses technicians were facing with moderate to severe stresses. The stress and fatigue scores in married ones were higher than the single ones. The results showed a significant relationship between smoking, stress, and fatigue scores (P<0.05). Conclusion: According to the high level of job stress in the dental prostheses technicians, this problem must be considered, minimized, and more attention should be paid to their psychological and emotional problems.